Targeted or Universal Coverage? Assessing Heterogeneity in the Effects of Universal Child Care - Kottelenberg, Michael J.; Lehrer, Steven F. (Journal of Labor Economics, 2017)
We provide evidence on the distributional effects of Quebec’s universal child care policy. Our analysis uncovers substantial policy relevant heterogeneity in the estimated effect of access to subsidized child care across two developmental score distributions for children from two-parent families. Whereas past research reported findings of negative effects on mothers and children from these families, igniting controversy, our estimates reveal a more nuanced image that formal child care can indeed boost developmental outcomes for children from some households: particularly disadvantaged single-parent households. We present suggestive evidence that the heterogeneity in policy effects is consistent with differences in home learning environments.